COMPARATIVE ANALYSIS OF THE LIFE QUALITY OF STUDENTS FROM ROMANIA AND THE EUROPEAN UNION - Alexandrina Mihaela POPESCU; Andreea Aurora Maria BUGA (Universitaria Publishing House, Craiova, 2024)
The concept of life quality is a construct concept, which is most often defined by the component elements and the interdependent relationships that are established between them. Crossing the pandemic period has led to the multiplication of studies on the quality of life, but most of the time these studies are carried out on adult or elderly subjects. We are trying to signal the importance of studying the quality of life of teenagers and young people, considering that the formation of healthy life skills can be formed more easily at these ages, which can lead to the formation of a healthy physical, mental, emotional and social. The study consists of the analysis of European and national level documents developed in recent years, in which the life quality of young people, respectively of students/master's students, is probed. We also try to identify the research on the life quality of young people carried out in recent years in the area of research of recent years.